2023
DOI: 10.1038/s41598-023-38140-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeted metabolomic profiling as a tool for diagnostics of patients with non-small-cell lung cancer

Ksenia M. Shestakova,
Natalia E. Moskaleva,
Andrey A. Boldin
et al.

Abstract: Lung cancer is referred to as the second most common cancer worldwide and is mainly associated with complex diagnostics and the absence of personalized therapy. Metabolomics may provide significant insights into the improvement of lung cancer diagnostics through identification of the specific biomarkers or biomarker panels that characterize the pathological state of the patient. We performed targeted metabolomic profiling of plasma samples from individuals with non-small cell lung cancer (NSLC, n = 100) and in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…found elevated plasma levels of phenylalanine in NSCLC and suggested that this may be due to abnormal inflammation and immune responses in tumors, which impair the function of phenylalanine hydroxylase ( 54 ). Similarly, two recent studies have reported increased levels of phenylalanine in the blood of lung cancer patients ( 55 , 56 ). In another metabolomic study, patients with lung cancer showed increased sputum levels of tyrosine compared to those with benign lung lesions, and a metabolic panel combining tyrosine with diethanolamine, cytosine, and lysine was proposed for the early diagnosis of lung cancer ( 46 ).…”
Section: Metabolomic Biomarkers For Cancer Screening and Diagnosismentioning
confidence: 66%
“…found elevated plasma levels of phenylalanine in NSCLC and suggested that this may be due to abnormal inflammation and immune responses in tumors, which impair the function of phenylalanine hydroxylase ( 54 ). Similarly, two recent studies have reported increased levels of phenylalanine in the blood of lung cancer patients ( 55 , 56 ). In another metabolomic study, patients with lung cancer showed increased sputum levels of tyrosine compared to those with benign lung lesions, and a metabolic panel combining tyrosine with diethanolamine, cytosine, and lysine was proposed for the early diagnosis of lung cancer ( 46 ).…”
Section: Metabolomic Biomarkers For Cancer Screening and Diagnosismentioning
confidence: 66%
“…There have been some studies of metabolomics in NSCLC diagnosis, characterization, and progression ( 20 ). However, the shortcomings of previous studies are the lack of standardized patient selection and few studies have focused on the value of metabolomics in predicting response or long-term survival in patients with lung cancer receiving immunotherapy.…”
Section: Discussionmentioning
confidence: 99%